Natural Compound Cudraflavone B Shows Promising Anti-inflammatory Properties in Vitro - KARTAL, MURAT; HOSEK, Jan; BARTOS, Milan; CHUDIK, Stanislav; DALL'ACQUA, Stefano; INNOCENTI, Gabbriella; Kartal, MURAT; KOKOSKA, Ladislav; KOLLAR, Peter; KUTIL, Zsofia; LANDA, Premysl; MAREK, Radek; et al. (My University, 2011)
Cudraflavone B (1) is a prenylated flavonoid found in large amounts in the roots of Morus alba, a plant used as a herbal remedy for its reputed anti-inflammatory properties. The present study shows that this compound causes a significant inhibition of inflammatory mediators in selected in vitro models: Thus, 1 was identified as a:potent inhibitor of tumor necrosis factor a (TNF alpha) gene expression and secretion by blocking the translocation of nuclear factor kappa B (NF-kappa B) from the cytoplasm to the nucleus in macrophages derived from a THP-1 human monocyte cell line. The NF-kappa B activity reduction resulted in the inhibition of cyclooxygenase 2 (COX-2) gene expression. Compound Cads as a COX-2 and COX-1 inhibitor with higher selectivity toward COX-2 than indomethacin. Pretreament of cells by 1 shifted the peak in an regulatory gene zinc finger protein 36 (ZFP36) expression assay. This natural product has noticeable anti-inflammatory properties suggesting that 1 potentially could be Used for development as a nonsteroidal anti inflammatory drug lead